Penerapan Teknik Relaksasi Benson pada Nyeri Akut Pasien Post Operasi Mastektomi di SMC RS Telogorejo - Surani Suci Pratiwi; Rahayu Winarti (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Acute pain is a common clinical problem experienced by patients after undergoing breast surgery such as Mastectomy, which may affect comfort, mobility, and recovery during the postoperative period. Effective pain management is essential in nursing care, and non-pharmacological approaches are increasingly utilized to complement pharmacological therapy. This study aimed to analyze the implementation of the Benson relaxation technique in reducing acute pain among post-mastectomy patients treated at Bougenville 1 Ward of SMC Telogorejo Hospital Semarang. The research employed an empirical clinical case study design involving four patients selected through purposive sampling based on predetermined inclusion and exclusion criteria. The intervention consisted of the Benson relaxation technique performed for 10–15 minutes daily for three consecutive days. Pain intensity was measured using the Numeric Rating Scale before and after each intervention session. The findings demonstrated a gradual decrease in pain intensity among all participants, shifting from moderate–severe pain before intervention to mild pain by the third day. These results suggest that Benson relaxation can serve as an effective complementary nursing intervention for postoperative pain management.